Can Tax Incentives Affect MSME Tax Compliance? - Budiman, Nita Andriyani; Nurkamid, Mukhamad; Sriyana , Jaka; Akhsyim (Future Science / FSH-PH Publications, 2022)
The government issued a tax incentive policy for the business sector. This policy was taken to help the public and business actors to survive in the middle period of the Covid-19 outbreak. The Covid-19 pandemic has influenced the relationship between tax incentives and MSME tax compliance. This study examines how much influence tax incentives have on MSME tax compliance. MSME actors get a total income tax incentive of 0.5% as referred to PP No. 23/2018 which is created by the government, where the taxpayers of MSME do not require to make tax deposits. During the Covid-19 pandemic, the government provided tax incentives that are expected to boost MSME tax compliance. The main objective of this study was to examine the impact of tax incentives on MSME tax compliance, using the Covid-19 situation as a moderating factor. The tax incentives in this study consist of knowledge of tax incentives and the use of tax incentives. The research data was obtained from UMKM in Kudus Regency with a sampling technique using purposive sampling. Data were collected from 231 respondents using a survey method. The data was analyzed using moderated regression analysis. The study's findings indicate that knowledge of tax incentives has a positive effect on MSME tax compliance, that use of tax incentives has no impact on MSME tax compliance, and that the Covid-19 pandemic has no influence on the relationship between knowledge of tax incentives and use of tax incentives on MSME tax compliance. The expected implication in this research is to be able to contribute to providing information about the compliance level of MSME taxpayers during the Covid-19 pandemic and to be used as evaluation material for the application of related policies.